All Days 2008
DOI: 10.2118/112355-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Agent for Formation-Damage Mitigation in Heavy-Oil Reservoir: Mechanism and Application

Abstract: Migration of formation fines has been shown to cause production decline in many wells, especially for sand production wells in heavy oil reservoir. Filter cakes in wire wrapped liner, which were formed by the attachment of viscous crude oil blended with formation fines, may block the flow paths of viscous oil. The solution to this problem is appropriate treatment to mitigate this type of formation damage.In this paper the performance at laboratory-scale of a new type of agent for formation damage mitigation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…A closely related surface activity was observed with all the brine solutions and slight increase in surface activity. The results of the combined salinity and temperature effect on surface activity and stability of rhamnolipid and Greenzyme show that the trend of surface activity is a function of brine composition but their respective surface activity is stable with increase in temperature which is consistent with other studies [11,17,[44][45][46]. Raheb and Hajipour [46] also observed rhamnolipid stability up to 100 • C, while Amani et al [44] and Amani [17] observed rhamnolipid stability at 120 • C. More so, Xu et al [45] also observed increase in surface activity of six protein samples investigated over a range of 23-60 • C temperature.…”
Section: Temperature Effectssupporting
confidence: 91%
See 2 more Smart Citations
“…A closely related surface activity was observed with all the brine solutions and slight increase in surface activity. The results of the combined salinity and temperature effect on surface activity and stability of rhamnolipid and Greenzyme show that the trend of surface activity is a function of brine composition but their respective surface activity is stable with increase in temperature which is consistent with other studies [11,17,[44][45][46]. Raheb and Hajipour [46] also observed rhamnolipid stability up to 100 • C, while Amani et al [44] and Amani [17] observed rhamnolipid stability at 120 • C. More so, Xu et al [45] also observed increase in surface activity of six protein samples investigated over a range of 23-60 • C temperature.…”
Section: Temperature Effectssupporting
confidence: 91%
“…They have also been identified as a good substitute for chemical surfactants in most applications in various fields such as environmental, biotechnological, food, medical processes as well as oil industries [3,7,8]. Also, past studies have reported enhanced oil recovery (EOR) potential of biosurfactants (e.g., [9][10][11][12][13][14][15][16][17]). However, most of these studies were not conducted with brine composition and salinity relevant to hydrocarbon reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there has been increased research on biologically generated surfactants (biosurfactants) as substitute for chemical surfactants and studies have reported the biosurfactants to be as efficient as chemical surfactants in different applications [27]. Also, past studies have reported EOR potential of biosurfactants (e.g., [22,[28][29][30][31][32][33][34]) but effect of biosurfactants on zeta potential of CORB system has not been explored. The main objective of this study, therefore, is to investigate the potential of synergy between CSB and biosurfactants for further improvement of oil recovery and to investigate their effect on rock-fluid interactions.…”
Section: Introductionmentioning
confidence: 99%
“… Wang et al (2008 ) conducted three core flooding experiments on three different handmade cemented rock samples using three enzyme concentrations (1, 2, and 5%). The oil was recovered from flooding in 90–95% of cases, and there was no significant recovery difference among the three enzyme concentrations; however, the most recovery was accomplished with 5%.…”
Section: Enzyme Applications In the Oil And Gas Industrymentioning
confidence: 99%